Nitrogen Uptake in the Northeastern Arabian Sea during Winter Cooling. (27th June 2010) - Kumar, S.; Ramesh, R.; Dwivedi, R. M.; Raman, M.; Sheshshayee, M. S.; D'Souza, W.
Abstract : The uptake of dissolved inorganic nitrogen by phytoplankton is an important aspect of the nitrogen cycle of oceans. Here, we present nitrate (N O 3 - ) and ammonium (N H 4 + ) uptake rates in the northeastern Arabian Sea using 15 N tracer technique. In this relatively underexplored region, productivity is high during winter due to supply of nutrients by convective mixing caused by the cooling of the surface by the northeast monsoon winds. Studies done during different months (January and late February-early March) of the northeast monsoon 2003 revealed a fivefold increase in the average euphotic zone integratedN O 3 - uptake from January (2.3 mmolNm − 2 d − 1 ) to late February-early March (12.7 mmolNm − 2 d − 1 ). Thef -ratio during January appeared to be affected by the winter cooling effect and increased by more than 50% from the southernmost station to the northern open ocean stations, indicating hydrographic and meteorological control. Estimates ofN O 3 - residence time suggested thatN O 3 - entrained in the water column during January contributed to the development of blooms during late February-early March.